Effects of Intrauterine Inflammation on Cortical Gray Matter of Near-Term Lambs - Stojanovska, Vanesa; Atik, Anzari; Nitsos, Ilias; Skiöld, Béatrice; Barton, Samantha K.; Zahra, Valerie A.; Rodgers, Karyn; Hooper, Stuart B.; Polglase, Graeme R.; Galinsky, Robert (Frontiers in Pediatrics, 2018)
Introduction: Ventilation of near-term lambs causes cerebral white matter inflammation and injury, which is exacerbated by intrauterine inflammation. However, the effects on the grey matter are not well-known. Our aim was to examine the effect of a ventilation strategy on the cerebral cortex with and without prior exposure to intrauterine inflammation. Method: Pregnant ewes at 119 ± 1 days gestation received an intra-amniotic injection of saline or lipopolysaccharide (LPS; 10mg/d). Seven days later, lambs were randomised to either; a high VT injurious ventilation strategy (INJSAL N=6, INJLPS N=5) or a protective ventilation strategy (PROTSAL N=5, PROTLPS N=6). Respiratory parameters and blood gases were monitored throughout. At post-mortem the brain was collected. Neuronal density (NeuN), apoptotic cell death (TUNEL), microglial density (Iba-1), astrocytic density (GFAP), and vascular protein extravasation (sheep serum) were all assessed using immunohistochemistry within the frontal, parietal, temporal and occipital lobes of the cerebral cortex. Results: A significant reduction in the number of neurons in all cortical layers except 4 was observed in LPS lambs compared to controls (layer #1: p=0.041; layers #2+3: p=0.023; layers #5+6: p=0.016) LPS treatment caused a significant increase grey matter area which is indicative of edema. LPS+ventilation did not cause apoptotic cell death in the grey matter. Astrogliosis was not observed following PROT or INJ ventilation, with or without LPS exposure. LPS exposure was associated vascular protein extravasation. Conclusion: Ventilation had little effect on grey matter inflammation and injury. Intrauterine inflammation reduced neuronal cell density, caused edema of the cortical grey matter, and blood vessel extravasation in the brain of near-term lambs.